Riverbank Filtration: Understanding Contaminant Biogeochemistry and Pathogen Removal - Ray, Chittaranjan (NATO Science Series, Series IV: Earth and Environmental Sciences, 2002)
Riverbank filtration is widely used in Europe and to some extent in the United States for the public water supply. It is a cost-effective and realisable treatment technology in which horizontal and vertical wells pump a mixture of ground water and induced surface water from a river. This book describes the biogeochemical issues involved in contaminant removal from surface water and the mechanisms of pathogen removal. Specifically, the following three points are considered: *The role of hydrogeological and well construction factors in the development of redox zones at bank filtration sites and the resulting impacts on contaminant removal. *The mechanisms of pathogen removal, including the processes, colloid filtration, die-away, decay, and predation. *The status of riverbank filtration processes in NATO partner countries